Silver in Iraqi Laws - Alhaddy , Heba Ghanim Dahi; Alnuaimy, Hiba Hazim Mohammed (Journal of Ecohumanism, 2025)
To learn about one of the innovations that the ancient Iraqis contributed to the entire world, as the ancient Iraqis excelled in various sciences and knowledge and were pioneers in many civilizational achievements that elevated human life towards the better. Among the most important of these innovations is the use of silver in commercial transactions, which influenced the nature of economic life in the ancient world and was mentioned in ancient laws. Material & methods: We relied on studying the metal silver and its importance in commercial transactions through ancient Iraqi laws as an analytical framework for the prevailing laws of that time. Results: The study results showed the importance of silver in commercial transactions instead of other perishable materials like barley. It also highlighted the value of this metal compared to other materials like barley, oil, and dates. Many laws mentioned silver in response to the negatives that existed in society at that time, stating that silver was paid as compensation in many cases.